Method for improving appearance reject ratio of foamed sole with metallic luster

In the production process of metal gloss foamed soles, metal color particles are premixed and two-stage feeding is processed with the sole raw materials, the problem of poor appearance of the sole is solved, and a more uniform color material distribution and lower Bad rate.

CN119502221APending Publication Date: 2025-02-25361 DEGREES (CHINA) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411997140.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing metallic foamed soles are prone to poor appearance during the production process, such as flow marks and stains, resulting in a high defect rate.

Method used

By placing metallic color particles and foamed sole raw materials, and mixing them in a mixing machine to form a metallic color sheet with a thickness of 1 mm-2 mm. Then mix with the first batch of raw materials in a mixer, the temperature is controlled at 115°C-125°C, and the feed is quickly discharged before the second batch of raw materials is put into use. Then, it is kneaded again on the starting mixer, and it is carried out for several times of thinning and thickening. Finally, it is poured into the granulator for granulation and foaming, and then molded.

Benefits of technology

Through this method, the appearance uniformity of the metallic gloss sole can be significantly improved, the defect rate can be reduced, and the appearance quality of the sole can be ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502221A_ABST
    Figure CN119502221A_ABST
Patent Text Reader

Abstract

The invention relates to the field of foamed shoe sole production and manufacturing, and provides a method for improving the appearance reject ratio of a foamed shoe sole with a metallic luster sense, and the method comprises the working procedures of material configuration, metallic color particle mixing, two-stage feeding and banburying, re-mixing, granulation, foaming and compression molding which are carried out in sequence. According to the invention, the metal color particles are subjected to pre-mixing treatment, and are dispersed in structure through temperature and continuous bundle stretching, so that the metal color particles are more easily fused with the main material of the sole raw material subsequently; meanwhile, the temperature of the color particle material is raised in advance, the fusion time of the subsequent pigment and the sole raw material main material in the internal mixer is shortened, then two-stage feeding is matched, the metallic luster sole with the uniform appearance is finally obtained, and the problems that a traditional foamed sole with the metallic luster is unstable in appearance and high in reject ratio are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sole production and manufacturing, and in particular to a method for improving the appearance defect rate of a foamed sole with a metallic luster. Background Art

[0002] Metallic luster soles are one of the most popular soles nowadays. The outer side or the whole of these soles presents a metallic luster, which can be produced by spraying paint on the outer surface or adding metallic pearl powder to the base material.

[0003] When a shoe sole with a metallic luster is formed by adding a metallic pearlescent powder colorant to a base material, the production process is mixing, granulating, foaming, and molding. In the mixing step, the metallic pearlescent powder colorant and other raw materials (except one or more of a foaming agent, a cross-linking agent, and an auxiliary agent) are mixed together once or multiple times, such as a shoe sole material with a metallic luster and a preparation method of a shoe sole with a metallic luster disclosed in a Chinese invention patent application with a publication number of CN118667258A, or a high-elastic shock-absorbing light-sensitive material and a preparation method thereof disclosed in a Chinese invention patent application with a publication number of CN118546455A.

[0004] The metallic glossy soles manufactured through the aforementioned process may have flow marks (water drop-shaped marks) or color spots on the appearance of some products, which are not uniform enough and result in a high rate of appearance defects. Therefore, further improvement is needed. Summary of the invention

[0005] The object of the present invention is to provide a method for improving the appearance defect rate of a foamed shoe sole with a metallic luster, which can overcome the defects in the prior art and reduce the appearance defect rate.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for improving the appearance defect rate of a foamed shoe sole with a metallic luster, comprising the following steps:

[0008] S1: preparing metallic color particles and raw materials for foamed soles, wherein the foaming agent, or the foaming agent and the bridging agent are used as the second batch of raw materials, and the materials other than the second batch of raw materials are used as the first batch of raw materials;

[0009] S2: using an open mill to mix and thin the metal color particles to obtain a metal color flake with a thickness of 1 mm to 2 mm;

[0010] S3: putting the first batch of raw materials and the metal color flakes into an internal mixer, mixing them to 115°C-125°C, stirring until the temperature of the raw materials drops to 110°C-115°C, then adding the second batch of raw materials, mixing until the temperature reaches 115°C-125°C, and then quickly discharging the materials;

[0011] S4: After the material is discharged, it is mixed on a mixer, and after multiple thinning and thickening processes, it is poured into a granulator for extrusion and granulation, and after standing, the granules to be foamed are obtained;

[0012] S5: foaming the to-be-foamed material particles to obtain a rough blank, and molding the rough blank.

[0013] Furthermore, the melting point of the metallic color particles is 115°C-125°C, and in step S1, the temperature of the mixing mill is set to 120°C-130°C.

[0014] Furthermore, in step S4, the mixing temperature on the mixer is 80°C-95°C.

[0015] Furthermore, in step S4, the temperature of extrusion granulation is 75°C-80°C.

[0016] Furthermore, the metallic color particles are particles formed by granulating metallic pearlescent powder with POE or EVA.

[0017] Furthermore, in the metallic color particles, the mass ratio of the metallic color pearlescent powder to POE or EVA is 1:5-6.

[0018] Furthermore, in step S5, the foaming temperature is 165±5°C, the foaming time is 8 to 12 minutes, and the molding temperature is 175±5°C.

[0019] Furthermore, in the raw material of the foamed sole, the content of EVA is ≥40% by mass.

[0020] Furthermore, the raw material of the foamed sole comprises auxiliary materials zinc oxide and zinc stearate, and the foaming agent is azodicarbonamide.

[0021] Furthermore, the foamed sole with metallic luster is composed of the following raw materials in parts by mass:

[0022] EVA 50~70 parts

[0023] Thermoplastic elastomer 15-25 parts

[0024] POE 15~25

[0025] 0.3-0.8 parts of stearic acid

[0026] Zinc stearate 0.3-0.8 parts

[0027] Zinc oxide 1.2-1.5 parts

[0028] Bridging agent 0.45~0.65 parts

[0029] 3-4 parts of foaming agent

[0030] 5 to 7 parts of metallic color particles.

[0031] After adopting the above technical solution, the present invention has the following advantages compared with the background technology:

[0032] The present invention performs a pre-mixing treatment on the metal color particles, disperses the structure of the metal color particles through temperature and continuous thinning and stretching, and makes it easier to subsequently fuse with the main material of the sole raw material; at the same time, the temperature of the color particle material is raised in advance, reducing the time for the subsequent color material to fuse with the main material of the sole raw material in the internal mixer, and then with the two-stage feeding, finally a metallic luster sole with uniform appearance is obtained, which improves the problem of unstable appearance and high defective rate of traditional foamed soles with metallic luster. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A schematic diagram of a sole product produced by the method for improving the appearance defect rate of a foamed sole with a metallic luster according to the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. It should be noted that in the specific implementation methods, the instruments, equipment, raw materials, reagents, etc. involved are all commercially available products or general products in the industry unless otherwise specified.

[0035] At present, the appearance of metallic soles will have flow marks or color spots, which are not uniform and uniform, and have a high defect rate. By using the same formula without adding colorants and the same process as the control group, it was found that no abnormal appearance phenomenon occurred. Therefore, the essence of the flow mark problem is that the metal colorant is unevenly distributed throughout the sole, that is, the colorant is not evenly dispersed / dissolved in other substrates. The inventor failed to achieve significant improvement by increasing the mixing time; the inventor also tried to increase the mixing temperature, but although the flow mark phenomenon was improved, the foaming ratio of the sole was difficult to reach the predetermined foaming ratio, resulting in a decrease in the quality of the finished product, and problems such as missing materials, rounded corners, and uneven surfaces, which is even more undesirable.

[0036] After repeated experiments and summary analysis, the present invention proposes a method for improving the appearance defect rate of a foamed sole with a metallic luster, wherein the foamed sole is a chemical foamed sole, and the method comprises the following steps:

[0037] S1: preparing metallic color particles and raw materials for foamed soles, wherein the foaming agent, or the foaming agent and the bridging agent are used as the second batch of raw materials, and the materials other than the second batch of raw materials are used as the first batch of raw materials;

[0038] S2: using an open mill to mix and thin the metal color particles to obtain a metal color flake with a thickness of 1 mm to 2 mm;

[0039] S3: putting the first batch of raw materials and the metal color flakes into an internal mixer, mixing them to 115°C-125°C, stirring until the temperature of the raw materials drops to 110°C-115°C, then adding the second batch of raw materials, mixing until the temperature reaches 115°C-125°C, and then quickly discharging the materials;

[0040] S4: After the material is discharged, it is mixed on an open mill, and after multiple thinning and thickening processes, it is poured into a granulator for extrusion and granulation, and after standing, the granules to be foamed are obtained;

[0041] S5: foaming the to-be-foamed material particles to obtain a rough blank, and molding the rough blank.

[0042] Through repeated experiments and summary analysis, the inventors found that the basic reason for the high appearance defect rate in the background of this case is that the melting index and / or dissolution temperature of the metal color particles and the main material (such as EVA or EVA and other thermoplastic elastomers, polyolefin elastomers) are different, resulting in only one of the two being dissolved / melted and dispersed during the material beating (mixing) process, and the other is not dissolved / melted and dispersed. Therefore, when one of the main materials / color particles fails to completely dissolve / melt and disperse during the material beating (mixing) process, the temperature in the foaming mold is sufficient to dissolve / melt and disperse it during the foaming process, resulting in the dissolution / melt dispersion and outflow, and the appearance of flow marks or color spots on the soles, and the degree of obviousness of the flow marks or color spots of each finished product is different, and it is impossible to effectively control it, resulting in a high appearance defect rate.

[0043] In the present invention, step S1 configures raw materials, and in the raw materials for the foamed sole, the foaming agent, or the foaming agent and the bridging agent are used as the second batch of raw materials, and the materials other than the second batch of raw materials are used as the first batch of raw materials. This is because the present invention improves the traditional one-stage feeding into a two-stage feeding, and before the second stage feeding, the first batch of raw materials (including main materials and auxiliary materials, excluding the foaming agent, or the foaming agent and the bridging agent) and the metallic colorant are evenly mixed.

[0044] After testing, the inventor found that the melting point of the metal color particles is 115-125℃, and the melt index is low. Therefore, step S2 is used to mix and thin it in advance on a small roller mill (a kind of open mill) (the machine setting temperature: 120℃-130℃, for example, 125℃), first adjust the thickness to 3mm-5mm, heat the metal color particles and mix them until they are fused (about mixing 2mmin-3min), then adjust the thickness to 1mmm-2mm, mix until they are completely fused (2min-3min); finally adjust the thickness of the sheet to 2mm, cut it into sheets of 15cm long×15cm wide×2cm thick, and then enter step S3.

[0045] In step S2, the metallic color particles are particles formed by granulating metallic pearlescent powder with POE (polyolefin elastomer) or EVA (ethylene-vinyl acetate copolymer), and the mass ratio of metallic pearlescent powder to POE or EVA is 1:5-6; the metal color particles are mixed and thinned because the color particles are composed of color powder and carrier (such as EVA or POE), and the melting index of the carrier and the color powder has a great influence on the fusion degree of the material, so the color particles are first beaten on the mixer until they are evenly dispersed, and the internal molecular structure of the material is stretched by temperature and continuous thinning to make its structure dispersed and easier to fuse with the main material of the sole raw material; at the same time, the temperature of the color particle material is raised in advance to reduce the fusion time of the color material with the main material in the internal mixer (such as the mixer), and prevent the foaming agent from foaming prematurely in the internal mixer due to the long dissolution time / temperature of the material. At the end of step S2, the metal color material sheet with a thickness of 1mm-2mm is warm when it is put into the internal mixer, and the temperature is 65℃-90℃.

[0046] In step S3, since the decomposition temperature of the foaming agent is 125-185°C, and since the sole raw material formula usually contains zinc oxide and zinc stearate, both of which can reduce the decomposition temperature of the foaming agent, it is selected to lower the material temperature before adding the foaming agent to prevent the foaming agent from reacting and decomposing in the internal mixer. The second batch of raw materials is added and mixed to a temperature of 115°C-125°C, and the material is quickly discharged, which also prevents the foaming agent from decomposing prematurely in the internal mixer, and the material is quickly discharged so that it stays at the temperature of the foaming agent decomposition for a period of time that is not long enough to reach the decomposition condition.

[0047] In step S4, the material quickly discharged from step S3 is put into an open mill (a type of mixer) for mixing at a mixing temperature of 80°C-95°C, thinned (2-3mm) 3-5 times, thickened (3-5mm) 2-3 times, and then poured into a granulator for granulation. After granulation, the material is placed in a cool and ventilated place to be stable for 12 hours. Specifically, the temperature of the front section of granulation extrusion is 80±5°C, the temperature of the middle section is 80±5°C, and the temperature of the back section is 75±5°C.

[0048] In step S5, the material particles to be foamed are poured into the foaming mold, the temperature of the upper and lower layers of the mold is set to 165±5°C, and the foaming time is 8-12min; after the foaming, the rough blank is cooled, sorted, packaged, and placed in a cool area for 12 hours before the next step of molding and shaping can be carried out. During the molding and shaping, the mold temperature is 175±5°C, the hot pressing time is 8-12min, and the cooling time is 8-12min. After trimming and finishing, the finished sole is obtained.

[0049] The method provided by the invention is applicable to EVA foamed soles, wherein the raw material of the foamed soles has an EVA content of ≥40% by mass. In the invention, the foaming agent may be azodicarbonamide, such as AC-6000.

[0050] The foamed shoe sole with metallic luster can be composed of the following raw materials in parts by mass:

[0051] EVA 50-70 parts, thermoplastic elastomer 15-25 parts, POE 15-25 parts, stearic acid 0.3-0.8 parts, zinc stearate 0.3-0.8 parts, zinc oxide 1.2-1.5 parts, bridging agent 0.45-0.65 parts, foaming agent 3-4 parts, metallic color particles 5-7 parts.

[0052] In a more specific embodiment, the selection and addition amount of each raw material are shown in Table 1.

[0053] raw material Raw material selection Addition amount (parts by mass) EVA first raw material Formosa Plastics 7350M 40 EVA second raw material Formosa Plastics 7470M 25 Thermoplastic elastomer TPE 1588 15 POE Dow POE 8003 20 Stearic acid(STE) 0.5 Zinc stearate 0.7 Zinc Oxide 1. 4 Bridging agent BIBP bridging agent 0.5 Foaming agent AC-6000 foaming agent 3.3 Metallic color particles Metallic pearlescent powder and POE granules 6.4

[0054] Table 1. Selection of raw materials in the embodiments of the present invention

[0055] The raw materials are weighed according to the weight of the formula ratio in Table 1: the main materials (EVA, thermoplastic elastomer, POE) are put in one batch, the metal color particles (the mass ratio of the metal color pearl powder to POE is 1:5, and the original color of the color particles is silver) are weighed separately, the auxiliary materials (stearic acid, zinc stearate, zinc oxide) are put in one batch, and the bridging agent and foaming agent are put in one batch. The metal color particles are mixed evenly on the mixer in advance according to step S2 and then put together with the auxiliary materials.

[0056] Use an air gun to blow clean the inner cavity of the liner until there is no residue, put the main material and auxiliary material into the inner cavity of the liner, press down with a heavy hammer, turn on the main machine and mix to 120℃. Raise the heavy hammer, stir the raw materials, and add the bridging agent / foaming agent after the temperature drops to 115℃, press down the heavy hammer, turn on the main machine, and quickly discharge the materials when the material temperature reaches 125℃.

[0057] After discharging, mix on the mixer. Thin (2-3MM) 3-5 times, thicken (3-5MM) 2-3 times, then pour into the granulator for granulation. The temperature of the front section of granulation extrusion is 80℃, the temperature of the middle section is 80℃, and the temperature of the back section is 75℃. After granulation, it needs to be placed in a cool and ventilated place to stabilize the material for 12 hours before foaming.

[0058] Pour the pellets to be foamed into the foaming mold, adjust the temperature of the upper and lower layers of the foaming mold to 165℃, and the foaming time is 550S. After the foaming, the rough blank is cooled, packaged, and placed in a cool area for 12 hours for secondary molding. The secondary molding mold temperature is 175℃, the hot pressing time is 550S, and the cooling time is 550S. The final sole (refer to Figure 1 ) The appearance has no flow marks and color spots, and the uniformity is good. And the specific gravity is 0.20g·cm- 3 , hardness is 55C, resilience is 48%, and compressibility is 45%.

[0059] like Figure 1 As shown, the present invention pre-mixes the metal color particles, disperses their structure through temperature and continuous thinning and stretching, and makes it easier to fuse with the main material of the sole raw material later; at the same time, the temperature of the color particle material is raised early to reduce the fusion time of the subsequent color material with the main material of the sole raw material in the internal mixer, and then cooperates with the two-stage feeding. Before the second stage of feeding, the first batch of raw materials (including main materials and auxiliary materials, excluding foaming agent, or foaming agent and bridging agent) and the metal color material flakes are mixed again and evenly, and then mixed with the foaming agent and the bridging agent; finally, a metallic luster sole with uniform appearance is obtained, and the defect rate of the method is less than 10%, which greatly improves the problem of unstable appearance and high defect rate of traditional foamed soles with metallic luster.

[0060] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for improving the appearance defect rate of a foamed shoe sole with a metallic luster, characterized in that: The following steps are involved: S1: preparing metallic color particles and raw materials for foamed soles, wherein the foaming agent, or the foaming agent and the bridging agent are used as the second batch of raw materials, and the materials other than the second batch of raw materials are used as the first batch of raw materials; S2: using an open mill to mix and thin the metal color particles to obtain a metal color flake with a thickness of 1 mm to 2 mm; S3: putting the first batch of raw materials and the metal color flakes into an internal mixer, mixing them to 115°C-125°C, stirring until the temperature of the raw materials drops to 110°C-115°C, then adding the second batch of raw materials, mixing until the temperature reaches 115°C-125°C, and then quickly discharging the materials; S4: After the material is discharged, it is mixed on a mixer, and after multiple thinning and thickening processes, it is poured into a granulator for extrusion and granulation, and after standing, the granules to be foamed are obtained; S5: foaming the to-be-foamed material particles to obtain a rough blank, and molding the rough blank.

2. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1, characterized in that: The melting point of the metallic color particles is 115°C-125°C. In step S2, the temperature of the mixing mill is set to 120°C-130°C.

3. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1, characterized in that: In step S4, the mixing temperature on the mixer is 80°C-95°C.

4. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1 or 2, characterized in that: In step S4, the temperature of extrusion granulation is 75°C-80°C.

5. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1 or 2, characterized in that: The metallic color particles are particles formed by granulating metallic pearlescent powder with POE or EVA.

6. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 4, characterized in that: In the metallic color particles, the mass ratio of the metallic color pearl powder to POE or EVA is 1:5-6.

7. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1, characterized in that: In step S5, the foaming temperature is 165±5°C, the foaming time is 8 to 12 minutes, and the molding temperature is 175±5°C.

8. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1, characterized in that: In the raw material for the foamed sole, the content of EVA is ≥40% by mass.

9. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1, characterized in that: The raw materials for the foamed sole include auxiliary materials zinc oxide and zinc stearate, and the foaming agent is azodicarbonamide.

10. The method for improving the appearance defect rate of a foamed shoe sole with a metallic luster according to claim 1 or 3, characterized in that: The foamed shoe sole with metallic luster is composed of the following raw materials in parts by mass: EVA 50~70 parts Thermoplastic elastomer 15-25 parts POE 15~25 0.3-0.8 parts of stearic acid Zinc stearate 0.3-0.8 parts Zinc oxide 1.2-1.5 parts Bridging agent 0.45~0.65 parts 3-4 parts of foaming agent 5 to 7 parts of metallic color particles.

Citation Information

Patent Citations

  • Sole material with metallic feeling and preparation method of sole with metallic feeling

    CN118667258A